Clinical Predictors of Delayed Discharges in Inpatient Mental Health Settings Across Ontario - Little, Jerrica (Adm Policy Ment Health, 2018)
Delayed discharges constitute an ongoing issue in psychiatric facilities. This study examined clinical predictors of 30-day delayed discharges in all designated inpatient mental health units within Ontario, Canada. Data for 76,184 inpatient episodes were obtained from 68 psychiatric facilities between 2011 and 2013. Risk factors for delayed discharges were analyzed using multivariate logistic regression. Indicators of functional, social, and cognitive impairment positively predicted delayed discharges, while symptoms of mental illness were inversely related. Policy makers and mental health care practitioners may utilize early predictors of delayed discharges to introduce treatment interventions and policies that reduce the risk of delays in mental health settings.